Book Launch, "The Making of a Blue Revolution in Bangladesh: Enablers, Impacts, and the Path Ahead for Aquaculture - Rashid, Shahidur; Zhang, Xiaobo; Dorosh, Paul; Minot, Nicholas (2020)
Shahidur Rashid, Xiaobo Zhang, Paul Dorosh, and Nicholas Minot BOOK LAUNCH The Making of a Blue Revolution in Bangladesh: Enablers, Impacts, and the Path Ahead for Aquaculture FEB 11, 2020 - 09:30 AM TO 11:00 AM EST